Early Orthodontic Treatment - Kukolj, Irena Đ.; Ivanović, Tanja; Ivanović, Dragan; Ragaj, Mirjana; Milosavljević, Vojislav; Nedić, Katarina (Medical Word, 2025)
Early orthodontic treatment is considered as treatment that begins and ends before all permanent teeth erupt, i.e. it is carried out in the period of milk and mixed dentition. Synonyms of early treatment are: preventive orthodontic treatment, interceptive orthodontic treatment or the first phase of comprehensive treatment. The aim of the work is to consider the advantages and disadvantages of early orthodontic therapy. It is necessary to carry out therapy that will lead to the desired facial aesthetics, increase the child’s confidence, parents’ satisfaction, enable simpler therapy in the future, a better and more stable result, enable the proper performance of orofacial functions, achieve more opportunities for skeletal growth modification and reduce potential iatrogenic damage. Based on an extensive diagnostic procedure, which includes: history, clinical examination, functional analysis, radiography and photography of the patient and analysis of study models, we come up with a therapy plan. The case report is a girl aged 9 years and 3 months. Early treatment should be carried out only in children who have a definite need for treatment. The group with a limited need should be given time for spontaneous correction.
Keywords: skeletal growth; interceptive orthodontic treatment; iatrogenic damage; AOA (active orthodontic appliances)